2023
DOI: 10.3390/ijerph20031921
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Students at Polish Universities after Two Years of the Outbreak of COVID-19

Abstract: Background: Mental health deterioration in young adults in the aftermath of the COVID-19 pandemic is being increasingly studied. It is clear that the psychological consequences of the pandemic will be evident for many years, especially among the younger generation, who did not have time to acquire adaptive coping strategies before the outbreak of COVID-19. The purpose of this study was to assess the condition of the mental health of students at Polish universities after two years of the pandemic. The types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…As COVID-19 disrupts communities around the world, further research and understanding of effective coping is crucial to reducing the short-and long-term impact of the pandemic on the psyche of young people. Female gender and professional inactivity appeared to be risk factors for the studentsʹ worsening mental health, which may be an indication of the need for further research and planning of psychotherapeutic interventions [41].…”
Section: Discussionmentioning
confidence: 98%
“…As COVID-19 disrupts communities around the world, further research and understanding of effective coping is crucial to reducing the short-and long-term impact of the pandemic on the psyche of young people. Female gender and professional inactivity appeared to be risk factors for the studentsʹ worsening mental health, which may be an indication of the need for further research and planning of psychotherapeutic interventions [41].…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a previous study conducted in the same city as the present study showed a prevalence of 8.6% of depressive symptoms among the general population [ 52 ]. Furthermore, women are twice as likely as men to suffer from anxiety and depression disorders [ 9 , 53 , 54 , 55 ]. Our findings corroborate these studies, since female university students reported the highest rates of anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%